Volcanic plume height monitoring using calibrated web cameras at the Icelandic Meteorological Office: system overview and first application during the 2021 Fagradalsfjall eruption - Talfan Barnie; Tryggvi Hjörvar; Manuel Titos; Eysteinn M. Sigurðsson; Sighvatur K. Pálsson; Bergur Bergsson; Þorgils Ingvarsson; Melissa Anne Pfeffer; Sara Barsotti; Þórður Arason; Vilhjálmur S. Þorvaldsson; Sibylle von Löwis of Menar; et al. (Journal of Applied Volcanology, 2023)
Abstract The Icelandic Meteorological Office maintains a national network of webcams designed and built in house for environmental monitoring. During the 2021 Fagradalsfjall eruption these cameras, along with a temporary near-field network of commercial cameras installed by the Department of Civil Protection and Emergency Management, were used to estimate the height of the $$SO_2$$ S O 2 plume and lava fountain. Here we present the webcam designs, the techniques used to calibrate them, and the messaging system and web interface that allow near real time measurements to be made from the images. With this system we were able to make estimates of heights with an accuracy on the order of tens to a few hundreds of meters with a lag typically of five to ten minutes at up to ten minute intervals when weather conditions were favorable. The plume heights were then used to constrain the performance of the $$SO_2$$ S O 2 dispersion model used for air quality forecasts while fountain heights were used to delineate danger zones where visitors at the eruption site were in danger of being hit by ballistic clasts.